2010
DOI: 10.1891/1933-3196.4.3.106
|View full text |Cite
|
Sign up to set email alerts
|

Emotionality of Loss-Related Memories Is Reduced After Recall Plus Eye Movements But Not After Recall Plus Music or Recall Only

Abstract: Numerous studies have shown that eye movements during recail of negative memories reduce their emotionaiity. We investigated whether these findings can be extended specificaliy to negative memories of loss. Sixty undergraduate students participated and recalled a negative autobiographical memory of loss and performed-in counterbalanced order-three types of tasks: recall-plus-eye-movements, recall-only, and recall-plus-relaxing-music. Recall-plus-music was added to investigate whether reductions in emotionality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…This competition within the working memory results in less memory resources for the vividness and the disturbance or emotionality of the memory (e.g. Andrade & Baddeley, 1997;Gunter & Bodner, 2008;Hornsveld, Landwehr, Stein, Stomp, Smeets, & van den Hout, 2010). Consistent with hypotheses from a working memory theory, memories have been found to not only becoming less disturbing, and less vivid, during execution of an eye movements task (e.g.…”
Section: Introductionmentioning
confidence: 60%
“…This competition within the working memory results in less memory resources for the vividness and the disturbance or emotionality of the memory (e.g. Andrade & Baddeley, 1997;Gunter & Bodner, 2008;Hornsveld, Landwehr, Stein, Stomp, Smeets, & van den Hout, 2010). Consistent with hypotheses from a working memory theory, memories have been found to not only becoming less disturbing, and less vivid, during execution of an eye movements task (e.g.…”
Section: Introductionmentioning
confidence: 60%
“…Finally, after recall þ EM and recall only, participants are asked to recall the memories again, and to rate vividness and emotionality once more. Studies have shown that recall þ EM reduces vividness and emotionality, but recall only does not (Andrade, Kavanagh, & Baddeley, 1997;van den Hout, Muris, Salemink, & Kindt, 2001;Kavanagh, Freese, Andrade, & May, 2001;Barrowcliff, Gray, Freeman, & MacCulloch, 2004;Kemps & Tiggemann, 2007;Maxfield, Melnyk, & Hayman, 2008;Gunter & Bodner, 2008). Apparently, the EM component of EMDR can be modeled under laboratory conditions, opening the door for the experimental dissection of the psychological mechanisms responsible for the treatment's therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…In a non-randomized controlled study, Sprang (2001) found that an EMDR group required significantly fewer sessions compared to the control condition of ‘guided mourning’ to achieve the same symptom reduction. In another study, participants who reported distressing memories following the death of a loved one (Hornsveld et al, 2010) had greater decline in emotionality of a grief-related memory following a recall plus eye movements condition compared to recall-only or recall with music condition.…”
mentioning
confidence: 97%